2020
DOI: 10.1002/ppul.24701
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status, intake, and outcomes in critically ill children with bronchiolitis

Abstract: Background Optimal nutrition in children with severe bronchiolitis remains poorly described. We aimed to describe nutritional status and practices in children with severe bronchiolitis requiring admission to the pediatric intensive care unit (PICU), and explore their associations with outcomes. Methods We conducted a retrospective study on patients with bronchiolitis requiring PICU stay from 2009 to 2014. Demographics, medical data, and baseline weight‐for‐length Z‐scores (WLZ) were collected. In patients requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Despite widespread use of enteral and parenteral nutrition in critically ill children, caloric and protein underfeeding continue to remain a common problem, including amongst the viral bronchiolitis population [ 12 , 13 ]. Malnutrition and nutrition deterioration are associated with longer duration of mechanical ventilation, longer PICU and hospital length-of-stay, higher risk of hospital-acquired infections, and increased mortality [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite widespread use of enteral and parenteral nutrition in critically ill children, caloric and protein underfeeding continue to remain a common problem, including amongst the viral bronchiolitis population [ 12 , 13 ]. Malnutrition and nutrition deterioration are associated with longer duration of mechanical ventilation, longer PICU and hospital length-of-stay, higher risk of hospital-acquired infections, and increased mortality [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…We will also compare total protein received by participants in the groups. We chose a separation of 0.5 g/kg/day protein as clinically meaningful based on our data from two cohorts of critically ill patients (bronchiolitis 27 and acute respiratory distress syndrome 9 ) which demonstrated that without supplementation, the median protein achieved within the first 3 days of illness was <1.0 g/kg/day and that 0.5 g/kg/day separation was associated with improved clinical outcomes, respectively. The number of participants who consented (or not) and completed (or discontinued early) the study and the reasons for non-consent/discontinuation will be summarised using counts and percentages.…”
Section: Methods and Analysismentioning
confidence: 99%
“…A retrospective study of 107 children with acute respiratory distress syndrome demonstrated significantly reduced mortality with energy intake ≥80% of predicted resting energy expenditure using the Schofield equation 19 and minimum protein intake of 1.5 g/kg by day 3 compared with patients who did not achieve these targets 51 . Conversely, protein intake of ≥1.5 g/kg on PICU day 3 was associated with significantly prolonged duration of mechanical ventilation and PICU length of stay in a retrospective study of 74 infants and young children with critical illness secondary to bronchiolitis 52 . These small studies demonstrating opposing outcomes with reference to 1.5 g protein/kg intake lack sufficient power to determine differences between groups.…”
Section: Timing Of Achievement Of Target Intake With En and Pnmentioning
confidence: 98%
“…51 Conversely, protein intake of ≥1.5 g/kg on PICU day 3 was associated with significantly prolonged duration of mechanical ventilation and PICU length of stay in a retrospective study of 74 infants and young children with critical illness secondary to bronchiolitis. 52 These small studies demonstrating opposing outcomes with reference to 1.5 g protein/kg intake lack sufficient power to determine differences between groups. The retrospective study designs also increase the risk of multiple uncontrolled variables, including the possibility of overfeeding impacting outcomes.…”
Section: Timing Of Achievement Of Target Intake With En and Pnmentioning
confidence: 99%